Role of Bangladesh Government in Making Accountability Effective (2009-Present) - Hossan, Md. Alomgir; Mahmud, Md. Sultan; Huda, Mahmudul (MultiTech Publisher, 2024)
The Bangladesh government has played a significant role in making accountability effective since 2009 through various initiatives and policies aimed at improving governance and transparency. In this study, we have endeavored to find out the problems and limitations of the government that hinder making the government accountable. Numerous Constitutional Provisions ensure accountability including Articles 55, 56, 70, 76, 77, 93, and 94. Governmental and Non-governmental institutions are also concerned with making the government accountable and answerable like the Right to Information Act. 2009, Anti-government Commission, Information and Communication Act, Transparency International Bangladesh (TIB), and so on. However, the government's commitment to promoting accountability and transparency is crucial in building public trust, fostering development, and combating corruption in the country. Finally, we proposed a model that will ensure accountability if the policymakers take it immediately.